Correlated Time‐Varying Magnetic Fields and the Core Size of Mercury. Issue 8 (21st August 2019) - Wardinski, I.; Langlais, B.; Thébault, E.
Abstract: Mercury is characterized by a very peculiar magnetic field, as it was revealed by the MESSENGER mission. Its internal component is highly axisymmetric, dominated by the dipole, and very weak. This in turns leads to a very dynamic magnetosphere. It is known that there exist relationships between the internally generated field and the external field, although their dynamics are complex. In this study we derive steady and time‐varying spherical harmonic models of Mercury's magnetic field using MESSENGER measurements and interpret these models both in terms of correlated features and of the internal structure of Mercury. The influence of the hemispheric data distribution of MESSENGER is evaluated to grant the robustness of our models. We find a quadrupole‐to‐dipole ratio of 0.27 for the steady magnetic field. The time‐varying models reveal periodic and highly correlated temporal variations of internal and external origins. This argues for externally inducing and internally induced sources. The main period is 88 days, the orbital period of Mercury around the Sun. There is no measurable time lag between variations of external and internal magnetic fields, which place an upper limit of 1 S/m for the mantle conductivity. Finally, the compared amplitudes of external and internal time‐varying field lead to an independent (from gravity studies) estimate of the conductive core radius, at 2, 060 ± 22 km. These analyses will be further completed with the upcoming BepiColombo mission and its magnetic field experiment, but the presented results already lift the veil on some of the magnetic oddities at Mercury. Key Points: We model Mercury's magnetic field with spherical harmonics We analyze time‐varying external (inducing) and internal (induced) magnetic fields We estimate Mercury's core size at 2, 060 km